تقصي مشكلات التكيف النفسي لدى المطلقين والمطلقات في محافظة شمال الباطنة بسلطنة عمان : دراسة حالة - شامسي، سيف خميس خلفان
Previous studies showed the absence of psychological adaptation leads to weakening the marriage relationship, which in return leads to divorce. Thus, the goal of this research to investigate the issue of psychological adaptation among divorced people. Employing a purposive sampling with case study design with total of four divorced persons participated in this study. An in-depth face to face individual interviews process was employed as the primary data collection in this qualitative research study. To answer each research questions, data were analyzed through coding, categorizing, and identifying sub-themes for the development of the main theme. The findings revealed main categories that cause a lack of adaptation: psychological, social, economic, physiological, ethical, emotional, and educational reasons. This study benefits the married couple for appropriate solutions in improving the marriage relationship through psychological adaptation in the positive marriage relationship. It is recommended that further examination that may serve couples for their relationship’s continuity and success to avoid the divorce.